2007
DOI: 10.1529/biophysj.107.104562
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of Ras Lipid Modifications Studied by 2H Solid-State NMR and Molecular Dynamics Simulations

Abstract: Human posttranslationally modified N-ras oncogenes are known to be implicated in numerous human cancers. Here, we applied a combination of experimental and computational techniques to determine structural and dynamical details of the lipid chain modifications of an N-ras heptapeptide in 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) membranes. Experimentally, 2H NMR spectroscopy was used to study oriented membranes that incorporated ras heptapeptides with two covalently attached perdeuterated hexadecyl cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 80 publications
3
44
0
Order By: Relevance
“…However, as pointed out in that study, polar and charged residues near the C-terminus may be located closer to the membrane than indicated by the spin labels, and distances from the membrane >5 Å are not determined unambiguously. Hence, it is very likely that all basic amino acids of myr-Src are indeed localized close to the headgroup region of the phospholipid membrane, supporting the above conclusion that additional short-range electrostatic interactions with anionic lipid headgroups contribute to membrane association of myrSrc (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). …”
Section: Secondary Structure and Membrane Topologysupporting
confidence: 52%
See 3 more Smart Citations
“…However, as pointed out in that study, polar and charged residues near the C-terminus may be located closer to the membrane than indicated by the spin labels, and distances from the membrane >5 Å are not determined unambiguously. Hence, it is very likely that all basic amino acids of myr-Src are indeed localized close to the headgroup region of the phospholipid membrane, supporting the above conclusion that additional short-range electrostatic interactions with anionic lipid headgroups contribute to membrane association of myrSrc (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). …”
Section: Secondary Structure and Membrane Topologysupporting
confidence: 52%
“…We have shown that myr-Src (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) interacts with zwitterionic membranes by partial insertion of its N-terminal myristoyl chain, where insertion depth and chain extent are dictated by a compromise between the hydrophobic effect and optimization of membrane packing on the one hand and Born repulsion and dehydration effects on the other. The interplay of these contributions results in a higher affinity of the Src peptide for DLPC than for DMPC, although the latter is expected to enable better hydrophobic matching.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies revealed that the linker domain is highly flexible and enables basic residues within the HVR and the G-domain of H-RAS to interact with membranes (Gorfe et al, 2007). A separate observation from the spectroscopy and modelling studies was that, in the context of the N-RAS targeting domain, the farnesyl group forms a stable anchor, whereas the palmitoyl group can flip in and out of the membrane (Vogel et al, 2007). Both our data and previous studies of H-RAS reveal that the N-and H-RAS Gdomains partially oppose the membrane interaction forces supplied by the HVR (Fig.…”
Section: Discussionmentioning
confidence: 98%